2017
DOI: 10.1016/j.imr.2017.01.002
|View full text |Cite
|
Sign up to set email alerts
|

Effectiveness and safety of combination treatment of herbal medicines and oral antihistamines for atopic dermatitis: a retrospective chart review

Abstract: BackgroundPatients with atopic dermatitis (AD) exhibit various symptoms, especially itching. Recently, herbal medicines (HMs) are being used in combination with antihistamines for the treatment of AD in Korea. While oral antihistamines can alleviate itching, HMs appear to exert anti-inflammatory effects with minimal side effects. However, there is little evidence regarding the effectiveness and safety of using HMs in combination with antihistamines for AD.MethodsTo observe the effectiveness and safety of combi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
6
0
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 10 publications
(7 citation statements)
references
References 29 publications
0
6
0
1
Order By: Relevance
“…We will recruit 36 mild-to-moderate AD patients for this study, scoring 30 to 80 points on a 100 mm VAS for pruritus (0, no symptom at all; 10, worst symptom ever) [27] and 10 to 40 points in the object SCORAD scores [28]. KM treatment such as acupuncture and herbal medicine may also relieve the symptoms of severe AD patients [12, 13]. However, in this trial, patients will receive only acupuncture treatment.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…We will recruit 36 mild-to-moderate AD patients for this study, scoring 30 to 80 points on a 100 mm VAS for pruritus (0, no symptom at all; 10, worst symptom ever) [27] and 10 to 40 points in the object SCORAD scores [28]. KM treatment such as acupuncture and herbal medicine may also relieve the symptoms of severe AD patients [12, 13]. However, in this trial, patients will receive only acupuncture treatment.…”
Section: Discussionmentioning
confidence: 99%
“…AD has been effectively treated with acupuncture, which has been shown to lack side effects when used with conventional therapies [1216]. In animal models, acupuncture treatment resulted in decreased skin overgrowth and pruritus and improved biomarkers [5, 17].…”
Section: Introductionmentioning
confidence: 99%
“…However, the safety profiles of HM as an adjuvant therapy in terms of herb-drug interaction need further studies. Although some studies have reported that the combination of CM such as oral antihistamines and HM in AD treatment was effective and safe [47], the interactions between herbs and CMs used in AD were largely understudied. For example, in the case of systemic immunosuppressive agents such as cyclosporine for severe AD, the administration of HM metabolized by the cytochrome P450 (CYP) system may affect its efficacy by changing the bioavailability of the drug.…”
Section: Discussionmentioning
confidence: 99%
“…16) Various herbal extract combinations were shown to be more effective dietary management agents in disease control. [17][18][19][20] Our previous study revealed that leaves of Lactuca sativa varieties (lettuce and romaine lettuce) played an acting in sleep promotion, 21) but the effects of lettuce on sleep architecture and relevant mechanism has yet been studied. In addition, although skullcapderived flavonoids are reported to bind to GABA receptor, 22) its study on sleep behavior has been limited.…”
mentioning
confidence: 99%